2014
DOI: 10.11648/j.ajce.20140201.11
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strengthening of Reinforced Concrete Beams Using Carbon Fiber Reinforced Polymer Laminate: A Review

Abstract: Several researches have been carried out on reinforced concrete beams strengthened with fiber reinforced polymer composite. Some of the works focused on shear strengthening compared with flexural strengthening that had the largest share. This paper reviews 10 articles on carbon fiber reinforced polymer strengthened reinforced concrete beams. Finally, this paper attempts to address an important practical issue that is encountered in shear strengthening of beams with carbon fibre reinforced polymer laminate. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…CFRP materials are multiphase systems, obtained artificially, by the association of at least two chemically distinct materials, with a clear separation interface between the components and the resulting compound material is created in order to obtain properties that cannot be obtained by any of the components working individually [9,10] The use of modern consolidation systems with polymeric composite materials reinforced with fibers in the structural rehabilitation of reinforced concrete elements and / or structures has well-known and documented advantages, such as: resistance to the action of corrosive agents (chlorine ions), high durability, superior mechanical characteristics (compared to classical materials), reduced execution time, etc.…”
Section: Structural Rehabilitation Using Cfrp Materials 41 General Re...mentioning
confidence: 99%
“…CFRP materials are multiphase systems, obtained artificially, by the association of at least two chemically distinct materials, with a clear separation interface between the components and the resulting compound material is created in order to obtain properties that cannot be obtained by any of the components working individually [9,10] The use of modern consolidation systems with polymeric composite materials reinforced with fibers in the structural rehabilitation of reinforced concrete elements and / or structures has well-known and documented advantages, such as: resistance to the action of corrosive agents (chlorine ions), high durability, superior mechanical characteristics (compared to classical materials), reduced execution time, etc.…”
Section: Structural Rehabilitation Using Cfrp Materials 41 General Re...mentioning
confidence: 99%
“…FE analysis was investigated and the results were verified with an experimental study, it was concluded that all different techniques of strengthening increased the ductility and strength of the walls. Alferjani et al [27] investigated the importance of using carbon fiber reinforced polymer (CFRP) sheets for RC beams shear strengthening. It was investigated that using CFRP sheets extended the service life of reinforced concrete structures and provided an economical solution.…”
Section: Coupled Shear Walls Strengthening Using Frp Laminatesmentioning
confidence: 99%
“…Li et al [12] determined that the variation in shear capacity of a strengthened beam depends strongly on the strengthened area. Alferjani et al [13] observed that an epoxy resin is favorable in strengthening and an end anchorage is needed to eliminate debonding failures. FRP-strengthened beams exhibit debonding failure modes at the end of the beams without an end anchorage and a rupture of the FRP in beams with an end anchorage [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%